Does Educational Handover Influence Subsequent Assessment?. (January 2021) - Dory, Valérie; Danoff, Deborah; Plotnick, Laurie H.; Cummings, Beth-Ann; Gomez-Garibello, Carlos; Pal, Nicole E.; Gumuchian, Stephanie T.; Young, Meredith
Abstract : Purpose: Educational handover (i.e., providing information about learners' past performance) is controversial. Proponents argue handover could help tailor learning opportunities. Opponents fear it could bias subsequent assessments and lead to self-fulfilling prophecies. This study examined whether raters provided with reports describing learners' minor weaknesses would generate different assessment scores or narrative comments than those who did not receive such reports. Method: In this 2018 mixed-methods, randomized, controlled, experimental study, clinical supervisors from 5 postgraduate (residency) programs were randomized into 3 groups receiving no educational handover (control), educational handover describing weaknesses in medical expertise, and educational handover describing weaknesses in communication. All participants watched the same videos of 2 simulated resident–patient encounters and assessed performance using a shortened mini-clinical evaluation exercise form. The authors compared mean scores, percentages of negative comments, comments focusing on medical expertise, and comments focusing on communication across experimental groups using analyses of variance. They examined potential moderating effects of supervisor experience, gender, and mindsets (fixed vs growth). Results: Seventy-two supervisors participated. There was no effect of handover report on assessment scores ( F (2, 69) = 0.31, P = .74) or percentage of negative comments ( F (2, 60) = 0.33, P = .72). Participants who received a report indicating weaknesses in communication generated a higher percentage of comments on communication than the control group (63% vs 50%, P = .03). Participants who received a report indicating weaknesses in medical expertise generated a similar percentage of comments on expertise compared to the controls (46% vs 47%, P = .98). Conclusions: This study provides initial empirical data about the effects of educational handover and suggests it can—in some circumstances—lead to more targeted feedback without influencing scores. Further studies are required to examine the influence of reports for a variety of performance levels, areas of weakness, and learners. Abstract : Supplemental Digital Content is available in the text.